Modulation of Excess Electron Transfer through LUMO Gradients in DNA Containing Phenanthrenyl Base Surrogates. Issue 9 (20th January 2017) - Roethlisberger, Pascal; Kaliginediand, Veerabhadrarao; Leumann, Christian J.
Abstract: The modulation of excess electron transfer (EET) within DNA containing a dimethylaminopyrene ( C ‐AP) as an electron donor and 5‐bromouracil ( Br dU) as an electron acceptor through phenanthrenyl pairs (phen‐R) could be achieved by modifying the phenanthrenyl base surrogates with electron withdrawing and donating groups. Arranging the phenanthrenyl units to form a descending LUMO gradient increased the EET efficiency compared to the electron transfer through uniform LUMOs or an ascending LUMO gradient. Abstract : Excess electron transfer (EET) can be modulated within DNA by introducing a dimethylaminopyrene ( C ‐AP) base surrogate as an electron donor, 5‐bromouracil ( Br dU) as an electron acceptor, and by changing the electronic nature of the phenanthrenyl pair.